2015
DOI: 10.1038/tp.2015.144
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide differential expression of synaptic long noncoding RNAs in autism spectrum disorder

Abstract: A genome-wide differential expression of long noncoding RNAs (lncRNAs) was identified in blood specimens of autism spectrum disorder (ASD). A total of 3929 lncRNAs were found to be differentially expressed in ASD peripheral leukocytes, including 2407 that were upregulated and 1522 that were downregulated. Simultaneously, 2591 messenger RNAs (mRNAs), including 1789 upregulated and 821 downregulated, were also identified in ASD leukocytes. Functional pathway analysis of these lncRNAs revealed neurological pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 73 publications
0
70
0
1
Order By: Relevance
“…Moreover, BDNF interacts with the TrkB receptor encoded by the NTRK2 gene, which has a paralog NTRK1 , already annotated as mutated in HSAN type IV [5,56,57]. In addition, it has been shown that the inhibition of BDNF-AS increases BDNF levels in vivo [38,58]. Modarresi et al recently showed that the knock-out of GDNF-AS increases the expression level of GDNF in human HEK293T cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BDNF interacts with the TrkB receptor encoded by the NTRK2 gene, which has a paralog NTRK1 , already annotated as mutated in HSAN type IV [5,56,57]. In addition, it has been shown that the inhibition of BDNF-AS increases BDNF levels in vivo [38,58]. Modarresi et al recently showed that the knock-out of GDNF-AS increases the expression level of GDNF in human HEK293T cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genome-wide studies identified thousand lncRNAs to be aberrantly expressed in peripheral leukocytes of ASD patients (Wang et al, 2015) as well as in ASD brain tissues (Ziats and Rennert, 2013). A comprehensive analysis of lncRNA co-expression relationships in drug-naive first-episode early-onset schizophrenia (EOS) patients showed that convergent lncRNA alteration may be involved in the etiologies of EOS (Ren et al, 2015).…”
Section: Lncrnas Play An Important Role In Neuropsychiatric Diseasesmentioning
confidence: 99%
“…With the rapid development of sequencing technologies [5], a series of dysregulated long non-coding RNAs (lncRNAs) have been found in many human diseases [6,7], especially in cancers [8,9]. Accumulating evidences suggested that long non-coding RNAs (lncRNAs) perform important or vital functions in the malignant tumors [10,11].…”
Section: Introductionmentioning
confidence: 99%